Kompetisi Dan Stabilitasperbankan Di Indonesia Suatu Pendekatan Analisis Panel Vector Autoregression - Intan Apriadi; Roy Sembel; Perdana Wahyu Santosa; Muhammad Firdaus (Jurnal Manajemen, 2017)
Bankingfragilityphenomenon in the world as well as in Indonesia whip outsome interesting issues to be investigated. The objective of this study is to investigate thedynamic causality relationship between competitionandstabilityof bankin Indonesia.The relationship between competition and stability of bank has long been a controversybefore some crises takes place in the world either in theoretical or in empirical sphere.The crucial questionsuch aswill competitionincrease stability of banking industry orthe other way around will competition create instability in banking system inIndonesiaaregoing tobe investigated in this study.Stability will be analyzed by z-score,and competition will be measuredby HHI. Testing the relationship between competitionand stability will be conducted by Panel Vector Autoregression, a relatively newapproach in econometrics.Empiricalresult indicates thatcompetitiondecreasedstabilityof banking industry,whereas stability has aninsignificant effect to competition.